Similarity in dissimilarity slippages in identity, race, place and belonging - Correa, Carolina Cerqueira (My University, 2018)
The core of my work is the dialog about racial identity and the slippages of belonging. The notion of identity in my work is within the Brazilian context and within the parameters of race. My research process involves self-portraiture, juxtaposition, layering, reinterpretation, and repetition. I create multiple compositions of my own identity in order to complicate existing interpretations of blackness through text, and images
Masters in Fine Art (by Research